TLCSD 2018
DOI: 10.30707/tlcsd2.2lieberman
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Graduate Student Stress in Speech Language Pathology

Abstract: Thus, the present study aimed to investigate SLP GS stress levels, the types of stressors experienced, and academic supports suggested as potentially helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Lieberman and colleagues also found that SLP graduate students rated exams, tuition, and time management as extremely stressful, while grades, papers, and frequent studying caused moderate stress. 13 In this study, 52% of SLP graduate students had moderate stress, while 44% indicated high stress on the Academic Stress Scale. It was noted that women tended to indicate higher stress levels and more stressrelated health problems, but stressed males were less likely to seek help for mental health issues.…”
Section: Student Clinician's Stress and Anxiety: Modeling Counseling mentioning
confidence: 57%
See 1 more Smart Citation
“…Lieberman and colleagues also found that SLP graduate students rated exams, tuition, and time management as extremely stressful, while grades, papers, and frequent studying caused moderate stress. 13 In this study, 52% of SLP graduate students had moderate stress, while 44% indicated high stress on the Academic Stress Scale. It was noted that women tended to indicate higher stress levels and more stressrelated health problems, but stressed males were less likely to seek help for mental health issues.…”
Section: Student Clinician's Stress and Anxiety: Modeling Counseling mentioning
confidence: 57%
“…Allied health programs, in general, are considered to be stressful due to constant academic and clinical evaluation. 12 Lieberman et al 13 noted that in the field of SLP, the required coursework, required clinical hours, breadth of clinical experiences, and scope of practice have all increased. There has also been a nationwide increase in college student referrals for counseling due to stress and anxiety, although this increase may be attributed to increased awareness of mental health and decreased stigma.…”
Section: Student Clinician's Stress and Anxiety: Modeling Counseling mentioning
confidence: 99%
“…While current trends suggest an overall increase in the number of adults diagnosed with mental illness, studies have also shown a similar trajectory for graduate student communities (Evans, Bira, Gastelum, Weiss, & Vanderford, 2018;Pedrelli, Nyer, Yeung, Zulauf, & Wilens, 2015). There is evidence to support generational differences in perception of mental health (Lieberman, Raisor-Becker, Sotto, & Redle, 2018). The survey concluded that Millennials (born between 1981-2000) and Gen Xers (born between 1965-1980 perceived higher levels of stress compared to older generations: Baby Boomer (born between 1946-1964) and Mature generations (born before 1945) (Lieberman, Raisor-Becker, Sotto, & Redle, 2018).…”
Section: Mental Health In the Undergraduate/graduate Populationsmentioning
confidence: 91%
“…There is evidence to support generational differences in perception of mental health (Lieberman, Raisor-Becker, Sotto, & Redle, 2018). The survey concluded that Millennials (born between 1981-2000) and Gen Xers (born between 1965-1980 perceived higher levels of stress compared to older generations: Baby Boomer (born between 1946-1964) and Mature generations (born before 1945) (Lieberman, Raisor-Becker, Sotto, & Redle, 2018). According to Hunt and Eisenberg (2010), almost half of college students satisfy the diagnostic criteria for at least one mental health disorder: 17% of undergraduate students met the criteria for depression, 12% met the criteria for an anxiety disorder, and the rest were categorized under the label of other mental health disorders.…”
Section: Mental Health In the Undergraduate/graduate Populationsmentioning
confidence: 99%
See 1 more Smart Citation